Review on green energy from microalgae - Sasirin Labua; Vanida Osiripun (Journal of Current Science and Technology, 2013)
Liquid fuels derived from petroleum have played a prominent role in our daily lives for centuries. Day after day, oil demand has been increasing because of increases in industrialization and population. Despite the many advantages of oil based fuels, there are many major disadvantages as well such as atmospheric pollution due to green house gases. Bioenergy is a clean energy and is one of the most important proposals to mitigate greenhouse gas emissions and substitute fossil fuels. Bioenergy can be an alternative energy source with the added benefit of fixing CO2 in the atmosphere through photosynthesis. Given the reliance on petroleum based fuels sources for most industrial machinery, finding an alternative is critical. Biodiesel fuel production from microalgae is technically feasible due to the highest yielding feedstock, short harvesting time and being exceedingly rich in oil.